Revolution, representation, and authoritarianism beyond Arab exceptionalism in Egypt - Wessel, Sarah (Routledge, Taylor & Francis Group, 2022)
This book examines Egypt’s turbulent and contradictory political period (2011-2015) as key to understanding contemporary politics in the country and the developments in the Arab region after the mass protests in 2010/11, more broadly. In doing so, it breaks new ground in the study of political representation, providing analytical innovation to the study of disenchantment with politics, democracy fatigue and social cohesion. Based on five years of intense fieldwork, the author provides rare insights into local and national ideas on politics, justice and identity, and on how people situate themselves and Egypt in the regional and global context. It analyzes how the creation of an alternate, political system was discussed and negotiated among the Egyptian population, the military, the government, public figures, the media, and international actors, and yet nevertheless today, Egypt has a new political regime that is the most repressive in the countries’ modern history. Finally, it recalls the emotions and perceptions of individuals and collectives and interlinks these local perspectives to national events and developments through time.
Literaturhinweise, Register
Keywords: Geschichte 2010-2022; Politik; Nationalcharakter; Arabischer Frühling; Ägypten; Arab Spring, 2010-; National characteristics, Egyptian; Revolutions / Arab countries / History / 21st century; Egypt / Politics and government / 2011-; Arab countries / Politics and government / 21st century